Synthesis, Characterization and in vitro Antibacterial Activity of Co(II), Cu(II) and Ni(II) Complexes with 4-Acylpyrazol-5-one Schiff Bases - Asegbeloyin1, J.N.; Agbo2, I.C.; Ukoha1, P.O.; Babahan3, I.; Okafor1, E.C. (Asian Journal of Chemistry, 2014)
The condensation reactions of 4-acylpyrazol-5-ones with some organic molecules with hydrazide moiety gave ONO and ONS donor Schiff base ligands. The ligands behaved as mono-anionic species when reacted with Co(II), Cu(II) and Ni(II) chlorides to form six co-ordinate ML2 type metal complexes. IR spectra show that the ligands act in a tridentate manner and coordinated ONO and ONS donor groups of the ligands to Ni(II), Cu(II) and Co(II) ions. The ligands and complexes were characterized by elemental analysis and spectroscopic methods, while the metal complexes were further characterized by conductivity and magnetic measurements. All the synthesized compounds were screened for their in vitro antibacterial activity against some Gram positive and Gram negative clinical bacterial strains. The metal complexes showed better antibacterial activity when compared to the Schiff bases.